The Implementation of Supply Chain Management Over Foreign Workers in Central Sulawesi, Indonesia - Lasatu, Asri; Sulbadana, Sulbadana; Surahman, Surahman; Insarullah, Insarullah; Asriyani, Asriyani (International Journal of Supply Chain Management, 2020)
Abstract- Global supply chains have become a common way of organizing investment, production and trade in the global economy. In many countries, particularly developing countries, they have created employment and opportunities for economic and social development. During the employment relationship, both the employers and the foreign workers must comply with the norms of employment while the local governments must cooperate with the Immigration Offices to supervise the employment of foreign workers. The purpose of this research was to find out about the implementation of supply chain management over foreign workers. The data was collected through observation, interviews, and literature review. The study was conducted in Palu City, Morowali Regency, and North Morowali Regency. The results showed that the supply chain management of foreign workers in Central Sulawesi Province had not been conducted optimally due to the lack of supervisors. On the other hand, the revocation of supply chain management by the regional government increasingly leads to the implementation of ineffective and inefficient control.